Plan estratégico para el mejoramiento del servicio comunitario de la Farmacia Javier, de la ciudad de El Empalme, para el período 2012 - 2016 - Ramírez León, Norma Carolina (2012)
This research was conducted in the city of the joint and usually aimed to develop a strategic plan related to pharmaceutical companies for the Pharmacy Javier, for community improvement, whose objectives is to develop an internal and external analysis of Javier Pharmacy, using SWOT tool, whether the pharmacy Javier has worked based on some form of strategic planning for the Pharmacy Javier. It was hypothesized general: Applying a strategic plan will benefit business development and encourage community support provided by the Pharmacy Javier, and specifically: the establishment of threats and opportunities by management, competitive strategy formulation will cause our corporate objectives are executed according to plan, the determination of the corporate vision and mission. Was determined as a result it is important for pharmacy Javier, have a strategic plan tailored to the business needs that can view the weaknesses. The research refers to the wave numbers 66.22% of the respondents stated that the main aspect of the pharmacy to improve is Javier extended hours, a 14.5% improvement in customer service, 10% believe that promotions are the aspect improve pre3sta services company, also note that the customer provided the pharmacy Javier the 72.16% is good, 20% very good. This seeks to improve and recover fully within the prescribed period.